Method for extracting lead-212 and bismuth-212 from thorium-232 decay chain
By adsorbing and leaching the lead-212 and bismuth-212 on the anion exchange column, the complex problem of resource waste and separation steps in the prior art is solved, and efficient and low-cost lead-212 and The separation of bismuth-212 ensures the maximum utilization of scarce nuclide resources.
Patent Information
- Application Number
- CN202411261811.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The prior art is difficult to extract lead-212 and bismuth-212 efficiently at the same time. There are waste of resources and complex separation steps when separating from the natural thorium-232 decay chain, and commonly used crown ether extractants are expensive and have water solubility problems.
Using silicon-based anion exchange resin, lead-212 and bismuth-212 in the solution containing halogen ions are adsorbed through an anion exchange resin column, and different leaching reagents are used to achieve their desorption and separation, avoiding adsorption of other nuclides, and simplifying Separation steps.
The rapid and selective separation and extraction of lead-212 and bismuth-212 from the natural thorium-232 decay chain is achieved, which improves product purity, reduces production costs, avoids product organic pollution, and is suitable for other complex nuclide systems. Separation.
Smart Images

Figure CN119120899A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of medical radioactive isotopes, and in particular relates to a method for extracting lead-212 and bismuth-212 from a thorium-232 decay chain. Background Art
[0002] In recent years, the incidence of cancer has increased year by year around the world, and cancer has become a serious threat to human life and health. Medical radioisotopes have important applications in cancer diagnosis and treatment, and are of great significance for ensuring people's life and health and social stability. 212 Pb / 212 Bi is one of the few radioactive isotopes that can be used in "targeted alpha nuclide therapy (TAT)", which has good efficacy in the treatment of malignant tumors such as ovarian cancer, pancreatic cancer, prostate cancer and breast cancer. However, its resources are very scarce, resulting in 212 The development and clinical application of Pb (lead) targeted drugs are severely restricted.
[0003] 212 Pb / 212 Bi is 232 Th decay products, separated and extracted from natural thorium 212 Pb / 212 Bi is expected to fundamentally solve the global 212 Pb / 212 Bi supply bottleneck problem, because it does not require reactors or accelerators, only relying on 232 The spontaneous decay of Th can produce sufficient 212 Pb / 212 Bi. 232 Th decay chain Figure 1 shown.
[0004] Separation and extraction from natural thorium 212 Pb / 212 Bi can be separated into direct separation method and indirect separation method. The so-called direct separation method refers to the selective extraction of Bi from natural thorium using highly selective adsorption materials. 212 Pb and 212 Bi for medical use; and indirect separation method refers to first 232 Separation of Th 228 Ra, and then separate step by step 228 Th, 224 Ra, finally with the help of 224 Ra / 212 Pb generator gets 212 Pb / 212 Bi. At present, there are many reports on indirect separation methods, and the technology is relatively mature. 224 Ra / 212Pb generator for 212 Pb / 212 Bi (half-life = 10.6 h) is more advantageous for large-scale distribution and transportation. However, this method also has its drawbacks, namely, the separation steps are complex and require multiple waiting times to allow the daughter to grow, and the separation products need to be purified and tested multiple times. This not only increases the risk of radiation hazards to personnel (especially short-lived radioactive gases are involved in the process), but also increases the risk of radiation hazards to personnel (especially short-lived radioactive gases are involved in the process). 220 Rn protection), but also leads to high production costs and long production cycles.
[0005] In comparison, the direct separation method is simple and efficient, and is very suitable for cities, counties, and even provincial administrative regions. 212 Pb / 212 However, the difficulty and key of this method lies in finding suitable separation materials and technologies to make 212 Pb and 212 Bi selectively from 232 Currently, there are reports that the selective separation of thorium from natural thorium can be achieved by using crown ether extractants based on solid phase adsorption (i.e., using Pb resin). 212 Pb targets, but cannot be extracted at the same time 212 Bi, resulting in a waste of scarce nuclide resources. In addition, crown ether extractants are very expensive and have a certain degree of water solubility. Before subsequent drug production, further separation and purification may be required to remove the dissolved crown ether. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for extracting lead-212 and bismuth-212 from the thorium-232 decay chain, which can simultaneously extract lead-212 and bismuth-212, and has a fast extraction speed, high purity, and is not easy to cause organic pollution of the product.
[0007] The embodiment of the present invention provides a method for extracting lead-212 and bismuth-212 from a thorium-232 decay chain. A solution containing a thorium-232 decay chain substance is passed through an anion exchange resin column. The solution containing the thorium-232 decay chain substance contains halogen ions, and the concentration of hydrogen ions in the solution containing the thorium-232 decay chain substance is greater than 0.01 mol / L (preferably, the concentration of hydrogen ions is 0.5-2 mol / L). Lead-212 and bismuth-212 are adsorbed by the anion exchange resin column, and other nuclides such as 228Ra, 228Ac, 232Th, etc. directly pass through the anion exchange resin column without being adsorbed. A washing reagent is introduced to desorb lead-212 and bismuth-212 from the anion exchange resin column, respectively, to separate and extract lead-212 and bismuth-212.
[0008] The thorium-232 decay chain includes the parent232 Th, including its decay daughters at all levels such as 228 Ra, 228 Ac, 228 Th, 212 Pb, 212 Bi, 208 Tl, etc. Figure 1 shown.
[0009] Preferably, the concentration of halogen ions in the solution containing thorium-232 decay chain substances is 0.3-4 mol / L, more preferably 0.5-2 mol / L.
[0010] Preferably, the thorium-232 decay chain substance is a thorium salt or a thorium oxide, more preferably a soluble salt containing thorium-232.
[0011] Preferably, the thorium salt is hydrated thorium nitrate.
[0012] Preferably, the halogen ions exist in the form of Cl - Br - or I - The acid or salt is preferably hydrochloric acid, hydrobromic acid or hydroiodic acid, and the concentration is preferably 0.3 to 4 mol / L, more preferably 0.3 to 2 mol / L. More preferably, it is hydrobromic acid or hydroiodic acid.
[0013] In a solution containing thorium-232 decay chain substances, the anions, except for halogen ions, cannot contain other anions exceeding the halogen ion concentration, otherwise competitive adsorption will occur, resulting in a deterioration in the selective adsorption effect of lead and bismuth.
[0014] When hydrochloric acid is used, the concentration of the hydrochloric acid is preferably 0.5 to 3 mol / L, more preferably 1 to 2 mol / L.
[0015] When hydrobromic acid is used, the concentration of the hydrobromic acid is preferably 0.3 to 2 mol / L, more preferably 0.3 to 1 mol / L.
[0016] When hydroiodic acid is used, the concentration of hydroiodic acid is preferably 0.5 to 3 mol / L, more preferably 0.5 to 1 mol / L.
[0017] Preferably, the anion exchange resin is a silica-based anion exchange resin.
[0018] Preferably, the preparation method of the silicon-based anion exchange resin is that 4-vinylpyridine and divinylbenzene are subjected to an in-situ solution copolymerization reaction in the presence of an initiator and a diluent in porous SiO2 channels to obtain silicon-based polyvinyl pyridine, and silicon-based polyvinyl pyridine is subjected to a methylation reaction with dimethyl sulfate to obtain the silicon-based anion exchange resin.
[0019] The initiator is a mixture of azobisisobutyronitrile and 1,1'-azobis(cyclohexanecarbonitrile), the diluent is acetophenone and diethyl phthalate, and the volume ratio of 4-vinylpyridine to divinylbenzene is 15-20:5-7.
[0020] The solvent for the methylation reaction is methanol-water solution, and the mass ratio of methanol to water is 1:1.
[0021] Preferably, the effective particle size of the silica-based anion exchange resin is 37-150 μm, and the BET specific surface area is 50-80 m 2 / g, and the average pore size is 10~50 nm.
[0022] Preferably, when separating lead-212, the eluting reagent is an aqueous solution having a salt concentration or an acid concentration less than 0.5 mol / L, more preferably ultrapure water; when separating bismuth-212, the eluting reagent is a nitric acid solution having a concentration greater than 0.5 mol / L, more preferably 1~2 mol / L HNO3.
[0023] Preferably, before the elution reagent is introduced, a solution containing halogen ions (preferably hydrochloric acid, hydrobromic acid or hydroiodic acid, preferably with a concentration of 0.5-1 mol / L) is introduced to elute out ions other than lead-212 and bismuth-212.
[0024] The beneficial effect of the present invention is that the present invention provides a method for obtaining a 232 Direct, rapid and selective separation of Th 212 Pb and 212 Bi's technical method. The present invention preferably uses a silicon-based anion exchange resin. Compared with conventional all-organic commercial resins, it has the advantages of fast adsorption / desorption speed, low column pressure, good hydraulic properties, etc., and is particularly suitable for the efficient separation and extraction of radioactive isotopes with a short half-life, such as 212 Pb (half-life 10.64 h) and 212 Bi (half-life is about 1 h). Experiments have shown that it is 212 Pb and 212 Bi has a high degree of adsorption selectivity and is basically not adsorbed 232 Therefore, the separation method using this silica-based anion exchange resin can effectively solve the traditional separation and extraction of crown ether materials. 212 The Pb method has many defects. This method can not only be applied to natural 232 Selective separation and extraction of Th decay chains 212 Pb and 212 Bi can also be applied to 228 Ra decay chain, 228 Th decay chain and224 Selective separation and extraction of Ra in the decay chain 212 Pb and 212 Bi can also be used in all other occasions involving the selective extraction of lead and bismuth from complex systems such as thorium, radium, actinium, lanthanum, barium, lead and bismuth.
[0025] The present invention provides a 232 Direct and rapid selective separation of Th from solution 212 Pb and 212 Bi's new method effectively avoids the use of expensive and water-soluble crown ether extractants. The obtained 212 The Pb sample has a very high purity and is basically free of impurity nuclides such as Th, Ac and Ra.
[0026] The material used in the present invention is a silicon-based anion exchange resin, which has the advantages of low price, fast adsorption / desorption kinetics, low column pressure, good hydraulic performance, stable chemical properties and not easy to dissolve, and can also achieve 232 Th decay chain 212 Pb and 212 The separation and extraction of Bi ensures the maximum utilization of scarce nuclide resources.
[0027] The present invention uses an acidic solution containing halogen ions to enable anion exchange resin to simultaneously and quickly adsorb 212 Pb and 212 Bi, but other metal elements are basically not adsorbed. When eluting, different eluents can be used to achieve 212 Pb and 212 The elution of Bi is achieved 212 Pb and 212 Separation of Bi, the separated product has high purity. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 for 232 Th and 232 The decay chain of U.
[0029] Figure 2 Comparison of the adsorption kinetics of SiPyR-N4 resin with commercial anion exchange resins IRA900 and PA316 resin.
[0030] Figure 3 The TOC content in SiPyR-N4 suspension changes with time.
[0031] Figure 4 This is the static adsorption behavior of SiPyR-N4 resin for different metal ions in hydrochloric acid medium.
[0032] Figure 5 Static adsorption behavior of SiPyR-N4 resin for different metal ions in hydrobromic acid medium.
[0033] Figure 6 Static adsorption behavior of SiPyR-N4 resin for different metal ions in hydroiodic acid medium.
[0034] Figure 7 Static adsorption behavior of SiPyR-N4 resin for different metal ions in nitric acid medium.
[0035] Figure 8 The static adsorption behavior of commercial IRA900 resin for different metal ions in hydrochloric acid medium.
[0036] Fig. 9 This is the static adsorption behavior of commercial PA316 resin for different metal ions in hydrochloric acid medium.
[0037] Fig.10 The figure shows a comparison of the elution effects of different eluents on lead.
[0038] Fig.11 The figure shows the comparison of eluting effects of different eluents on bismuth.
[0039] Fig.12 For the separation of Pb, Bi from Th, La and Ba; Wherein, I: dead volume; II: mixed metal solution; III: 1.0 M HCl solution; IV: ultrapure water; V: 1.0 MHNO3.
[0040] Fig.13 For solid 232 Th(a) and the separated 212 Pb(b) and 212 Comparison of γ-ray spectra of Bi (c) samples, where (a) is solid 232 γ spectrum of Th, (b) is the separated 212 γ spectrum of Pb solution, (c) is the separated 212 Gamma spectrum of Bi solution. DETAILED DESCRIPTION
[0041] Example 1 The anion exchange resin is a silica-based anion exchange resin, and its preparation is divided into two steps. Step 1: Synthesis of silicon-based polytetravinylpyridine (SiPyR-N3) First, 100 g of porous SiO2 particles were added to the flask of the rotary evaporator. The flask was kept rotating at a low speed. The oxygen in the rotary evaporator was replaced twice with nitrogen, and then the vacuum was evacuated to 20 hPa. At the same time, 45 mL of ACP (acetophenone), 30 mL of DEP (diethyl phthalate), 17.69 mL of 4-vinylpyridine, 6.41 mL of DVB (divinylbenzene), 0.3215 g of AIBN (azobisisobutyronitrile) and 0.2144 g of V-40 (1,1'-azobis(cyclohexanecarbonitrile)) were mixed in sequence. After the initiators AIBN and V-40 were completely dissolved, the mixed oil phase was introduced into the rotary evaporator flask using the pressure difference. The rotation speed was adjusted and the wall of the flask was gently tapped to fully mix the oil phase with the SiO2 until there was no obvious agglomeration. At this time, it can be considered that the oil phase has completely entered the interior of the SiO2. Nitrogen was filled to restore to normal pressure, and then the temperature was raised to start the polymerization reaction. Oil bath heating was used, and the temperature was maintained at 60°C for 1 h, 70°C for 2 h, 80°C for 2 h, and 90°C for 13 h. After the reaction, acetone and ultrapure water were used to wash twice alternately. The product was named SiPyR-N3 and was placed in a vacuum drying oven at 40°C for 48 h for later use.
[0042] Step 2: Preparation of silicon-based anion exchange resin SiPyR-N4 using SiPyR-N3 as precursor Take an appropriate amount of SiPyR-N3 resin and 500 g of methanol / water (mass ratio of 1:1) and add them successively to a dry 250 mL three-necked flask equipped with a stirring paddle and a dropping funnel. Use a water bath to heat and maintain the reaction temperature at about 25°C. Then measure 3 times the molar amount of dimethyl sulfate contained in the SiPyR-N3 resin in the bottle, control the flow rate with a dropping funnel and slowly add it to the bottle. Stir at a low speed and use 10 M sodium hydroxide solution to control the pH value of the solution at neutral. When the pH of the solution gradually stabilizes and no longer changes, continue to add 2 times the molar amount of dimethyl sulfate contained in the SiPyR-N3 resin in the bottle. Continue to control the pH value to maintain the reaction under neutral conditions. After the reaction is completed, the product is named SiPyR-N4 and rinsed alternately with acetone and ultrapure water twice each. After that, continue to wash with 5M NaCl solution and ultrapure water to convert SiPyR-N4 into chlorine type. Finally, the transformed SiPyR-N4 was placed in a vacuum drying oven and dried at 40°C for 48 hours for later use.
[0043] The quaternized strongly alkaline silica-based anion exchange resin SiPyR-N4 has a functional group of 1-methylpyridine, an effective particle size of 37-150 μm, an organic component of about 25.5%, and a BET specific surface area of about 52.2 m 2 / g, and the average pore size is 36.8 nm.
[0044] Example 2 The adsorption speed comparison experiment of different resins is as follows: (1) Dissolve a certain amount of bismuth nitrate in 1.0 M HCl to prepare a mixed working solution containing 1.0 M HCl and 500 mg / L Bi.
[0045] (2) Take some clean 40 mL glass bottles and add 0.05 g of the resin of Example 1 to each bottle. Take another 20 mL of the mixed working solution and add it to the above glass bottles. Cover the bottle with a lid and place it in a 25°C water bath shaker for shaking at a frequency of 120 rpm.
[0046] (3) Set different mixing contact times, and immediately use a microporous filter membrane to separate the solid and liquid after the sample reaches the time node.
[0047] (4) The solution before and after adsorption was diluted with dilute nitric acid to an appropriate concentration, and then the concentration of Bi in the solution was measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The adsorption efficiency of the resin was determined based on the difference in concentration before and after adsorption, and an adsorption kinetic curve showing the change of adsorption efficiency over time was plotted.
[0048] (5) The adsorption kinetics of commercial strong alkaline anion exchange resins IRA900 and PA316 were evaluated by the same method as in steps (1) to (4), and the adsorption rates were compared.
[0049] IRA900 resin is a commercially available strongly basic anion exchange resin produced by Dow Chemical Company of the United States. Its skeleton structure is styrene-divinylbenzene copolymer and its functional group is trimethyl quaternary ammonium salt.
[0050] PA316 resin is a commercially available strongly alkaline anion exchange resin produced by Mitsubishi Resins Co., Ltd. of Japan. Its skeleton structure and functional groups are consistent with those of IRA900 resin.
[0051] The experimental results are as follows Figure 2 As shown, the resin of Example 1 basically reaches adsorption equilibrium within 10 minutes, while IRA900 and PA316 resins need more than 120 minutes to reach adsorption equilibrium. The adsorption speed of the resin of Example 1 is significantly faster than that of commercial anion exchange resin.
[0052] Example 3 The chemical stability experiment of the resin of Example 1 comprises the following steps: (1) Take a batch of clean glass bottles, add 0.1 g of the resin of Example 1 into each glass bottle, then transfer 30 mL of 1.0 M HCl solution to mix with the resin and seal the bottle with a lid.
[0053] (2) Place the batch of glass bottles in a 25°C constant temperature water bath shaker and oscillate at a frequency of 120 rpm.
[0054] (3) Different mixing contact times are set, and after reaching the time point, the sample is immediately filtered through a microporous filter membrane for solid-liquid separation.
[0055] (4) Use a total organic carbon (TOC) analyzer to analyze the TOC content in the solution and draw a curve of the change of TOC with contact time.
[0056] The experimental results are as follows Figure 3 As shown, the TOC content in the solution has basically no significant change with time, proving that the resin in Example 1 has good chemical stability and is insoluble in water.
[0057] Example 4 The selective adsorption experiment steps are: (1) Weigh a certain amount of thorium nitrate, lead nitrate, bismuth nitrate, lanthanum nitrate, and barium nitrate, and dissolve them in HCl media of different concentrations to prepare a mixed solution containing 100 mg / L Th, 90 mg / L Pb, 90 mg / L Bi, 60 mg / L La, and 60 mg / L Ba.
[0058] (2) Take some clean 40 mL glass bottles, add 0.05 g of the resin of Example 1 to each bottle, and transfer 20 mL of the mixed solution to the glass bottle. Cover the bottle with a lid and place it in a 25°C water bath shaker for shaking at a frequency of 120 rpm. Here, the stable 207 Pb is used to simulate 232 The Th decay chain 212 Pb; stable 209 Bi is used to simulate 232 The Th decay chain 212 Bi; La has similar chemical properties to Ac and is used to simulate 232 The Th decay chain 228 Ac; Ba and Ra have similar chemical properties and are used to simulate 232 The Th decay chain 224 Ra and 228 Ra.
[0059] (3) After oscillating for 2 h, the sample was separated into solid and liquid using a microporous filter membrane.
[0060] (4) The solution before and after adsorption was diluted with dilute nitric acid to an appropriate concentration, and then the concentration of each metal element in the solution was measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The adsorption efficiency of the resin for different metal elements was determined based on the difference in the concentration of each metal element before and after adsorption.
[0061] (5) The above steps (1-4) were also used to investigate the adsorption behavior of SiPyR-N4 resin in hydrobromic acid and hydroiodic acid media.
[0062] The experimental results are as follows Figure 4 , Figure 5 and Figure 6 As shown, the resin of Example 1 exhibits unique adsorption selectivity for Pb and Bi in the three acid media, and does not adsorb Th, Ba and La elements.
[0063] from Figure 4-6 It can be seen that during static adsorption, the anion exchange resin mainly adsorbs Bi in the hydrochloric acid medium, and also adsorbs a small amount of Pb, and basically does not adsorb other ions, such as La, Th and Ba. In the hydrobromic acid medium, the resin mainly adsorbs Bi and Pb, but the adsorption effect is better in low concentrations of hydrobromic acid than in high concentrations of hydrobromic acid. When it exceeds 3 mol / L, the adsorption effect of the resin on Bi and Pb will decrease. The resin also mainly adsorbs Bi and Pb in the hydroiodic acid medium, and the resin has a better adsorption effect in low concentrations of hydroiodic acid than in high concentrations of hydroiodic acid. When it exceeds 2 mol / L, the adsorption of Bi and Pb by the resin will decrease.
[0064] Comparative Example 1 Compared with Example 4, the difference is that step (1) is: weigh a certain amount of thorium nitrate, lead nitrate, bismuth nitrate, lanthanum nitrate and barium nitrate, and dissolve them in HNO3 medium with different concentrations. The rest is the same as Example 4.
[0065] The experimental results are as follows Figure 7 As shown, the silicon-based anion exchange resin does not adsorb any metal ions in the HNO3 medium, which means that the selective separation of lead and bismuth cannot be achieved. It can be seen that Example 4 is more suitable for the selective separation of lead and bismuth in the solution system than Comparative Example 1.
[0066] Example 5 The adsorption behavior of different anion exchange resins on thorium, lead, bismuth, lanthanum and barium in hydrochloric acid medium was compared. The steps are as follows: (1) Weigh a certain amount of thorium nitrate, lead nitrate, bismuth nitrate, lanthanum nitrate, and barium nitrate, and dissolve them in HCl media of different concentrations to prepare a mixed solution containing 100 mg / L Th, 90 mg / L Pb, 90 mg / L Bi, 60 mg / L La, and 60 mg / L Ba.
[0067] (2) Take some clean 40 mL glass bottles, add 0.05 g of IRA900 resin to each bottle, and transfer 20 mL of the mixed solution to the bottle. Cover the bottle with a lid and place it in a 25°C water bath shaker for shaking at a frequency of 120 rpm.
[0068] (3) After oscillating for 2 h, the sample was separated into solid and liquid using a microporous filter membrane.
[0069] (4) The solution before and after adsorption was diluted with dilute nitric acid to an appropriate concentration, and then the concentration of each metal element in the solution was measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES). The adsorption efficiency of the resin for different metal elements was determined based on the difference in the concentration of each metal element before and after adsorption.
[0070] (5) The above steps (1-4) were also used to investigate the adsorption behavior of IRA900 resin and PA316 resin in hydrochloric acid medium, and compared with the adsorption behavior of SiPyR-N4 for the above metal elements.
[0071] The experimental results are as follows Figure 8 and Fig. 9 As shown in the figure, the anion exchange resins produced by three different companies all have the same adsorption behavior, that is, they can selectively adsorb lead and bismuth under the experimental conditions, so they can all be used in natural 232 Th decay chain 212 Pb and 212 Selective separation of Bi.
[0072] Example 6 The lead elution experiment steps are: (1) Take some SiPyR-N4 resin from Example 1 and fill it in a Fill the glass adsorption column until it is full.
[0073] (2) Using a bottom-up flow mode, first introduce ultrapure water to remove bubbles and adjust the flow rate to 1.0 mL / min.
[0074] (3) Pretreat the resin column by passing 50 mL of 1.0 M HCl.
[0075] (4) Weigh a certain amount of lead nitrate and dissolve it in 1.0 M HCl to prepare a hydrochloric acid solution containing 90 mg / L Pb.
[0076] (5) About 45 mL of the above lead solution was introduced, followed by 50 mL of ultrapure water, and the lead concentration in the effluent was measured by ICP-AES.
[0077] (6) Repeat the above steps (1-4), and replace the ultrapure water in step (5) with 0.1 M HCl and 0.01 M HCl, respectively, and compare the elution effect of ultrapure water and dilute acid solution on lead.
[0078] The experimental results are as follows Fig.10 As shown in the figure, compared with 0.1 M HCl and 0.01 M HCl, ultrapure water can elute lead more easily and achieve a higher enrichment multiple.
[0079] Example 7 The elution experiment of bismuth is as follows: (1) Take some SiPyR-N4 resin from Example 1 and fill it in a Fill the glass adsorption column until it is full.
[0080] (2) Using a bottom-up flow mode, first introduce ultrapure water to remove bubbles and adjust the flow rate to 1.0 mL / min.
[0081] (3) Pretreat the resin column by passing 50 mL of 1.0 M HCl.
[0082] (4) Weigh a certain amount of lead nitrate and dissolve it in 1.0 M HCl to prepare a hydrochloric acid solution containing 90 mg / L Bi.
[0083] (5) About 45 mL of the above Bi solution was introduced, followed by 100 mL of 1.0 M HNO3 solution. The Bi concentration in the effluent was measured by ICP-AES.
[0084] (6) Repeat the above steps (1-4), and replace the ultrapure water in step (5) with 3 M HNO3 and 0.1 M HNO3, respectively, and compare the elution effect of 1.0 M HNO3 and other concentrations of nitric acid solutions on bismuth.
[0085] The experimental results are as follows Fig.11 As shown in the figure, compared with 3.0 M HNO3 and 0.1 M HNO3, 1.0 M HNO3 can elute Bi more easily and achieve a higher enrichment multiple. On the contrary, 0.1 M HNO3 can hardly achieve complete elution of Bi.
[0086] Example 8 The cold simulated separation experiment has the following steps: (1) Take some of the resin from Example 1 and fill it in a Fill the glass adsorption column until it is full.
[0087] (2) Using a bottom-up flow mode, first introduce ultrapure water to remove bubbles and adjust the flow rate to 1.0 mL / min.
[0088] (3) Pretreat the resin column by passing 50 mL of 1.0 M HCl.
[0089] (4) Weigh a certain amount of thorium nitrate, lead nitrate, bismuth nitrate, lanthanum nitrate, and barium nitrate, and dissolve them in 1.0 M HCl to prepare a mixed solution containing 100 mg / L Th, 90 mg / L Pb, 90 mg / L Bi, 60 mg / L La, and 60 mg / L Ba.
[0090] (5) About 45 mL of the above mixed solution is introduced. At this time, Pb and Bi are simultaneously fixed on the resin column, while other elements such as thorium, lanthanum, and barium directly pass through the resin column.
[0091] (6) Pass 15 mL of 1.0 M HCl solution to elute the thorium, lanthanum, and barium remaining on the resin column.
[0092] (7) Pass 25 mL of ultrapure water to desorb the Pb adsorbed on the resin column.
[0093] (8) Pass 50 mL of 1.0 M HNO3 solution to desorb the Bi fixed on the resin column.
[0094] (9) The effluent was collected by a fraction collector, and the collection time of each centrifuge tube was set to 5 min. The concentration of each metal element in each centrifuge tube was measured by ICP-AES.
[0095] The experimental results are as follows Fig.12 As shown, the resin column of Example 1 can selectively fix Pb and Bi in the mixed metal solution, but does not substantially adsorb Th, Ba and La. Pb and Bi are successfully separated from the Th solution and recovered separately.
[0096] Example 9 The hot separation experiment steps are: (1) Take some of the resin from Example 1 and fill it in a Fill the glass adsorption column until it is full.
[0097] (2) Using a bottom-up flow mode, first introduce ultrapure water to remove bubbles and adjust the flow rate to 1.0 mL / min.
[0098] (3) Pretreat the resin column by passing 50 mL of 1.0 M HCl.
[0099] (4) Weigh 2.0 g of hydrated thorium nitrate and dissolve it in 45 mL of 1.0 M HCl.
[0100] (5) About 45 mL of the above mixed solution is introduced. At this time, Pb and Bi are simultaneously fixed on the resin column, while other elements such as thorium, actinium, and radium directly pass through the resin column.
[0101] (6) Pass 15 mL of 1.0 M HCl solution to elute the thorium, actinium, and radium remaining on the resin column.
[0102] (7) Pass 25 mL of ultrapure water to remove the adsorbed 212 Pb is desorbed.
[0103] (8) Pass 50 mL of 1.0 M HNO3 solution to fix the 212 Bi is desorbed.
[0104] (9) Take the collected 212 The Pb samples were analyzed by γ spectrum and compared with 232 At the same time, ICP-AES analysis was used to compare the γ spectrum of Th. 212 Th concentration in Pb samples.
[0105] The experimental results are as follows Fig.13 As shown, with solid 232 Compared with the γ energy spectrum peak of Th, the 212 Pb and 212 Bi sample has fewer nuclide γ spectrum peaks. 232 Trace amounts of Th in the decay chain 224 Ra and 228 Ac was completely removed, and 212 Pb and 212 Bi is basically retained and has a high purity. The ICP-AES measurement results show that 212 Pb and 212 The concentration of thorium in the Bi sample solution was 0 mg / L, which was below the instrument detection limit, proving that 232 Th and 228 Th is completely removed. Therefore, combined with Example 4, the experiment successfully proved that this method can be used to directly remove 232 Selective extraction from Th decay chains 212 Pb and 212 Bi.
[0106] A person skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of protection of the present application is limited to these examples. In line with the concept of the present application, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of different aspects of one or more embodiments of the present application as described above, which are not provided in detail for the sake of simplicity.
[0107] One or more embodiments of the present application are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the present application. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of one or more embodiments of the present application should be included in the protection scope of the present application.
Claims
1. A method for extracting lead-212 and bismuth-212 from the thorium-232 decay chain, characterized in that: A solution containing thorium-232 decay chain substances is passed through an anion exchange resin column, wherein the solution containing thorium-232 decay chain substances contains halogen ions, and the concentration of hydrogen ions in the solution containing thorium-232 decay chain substances is greater than 0.01 mol / L, lead-212 and bismuth-212 are adsorbed by the anion exchange resin column, while other nuclides directly pass through the anion exchange resin column without being adsorbed, and a washing reagent is introduced to desorb lead-212 and bismuth-212 from the anion exchange resin column, respectively, to separate and extract lead-212 and bismuth-212.
2. The method according to claim 1, wherein: The concentration of halogen ions is 0.3~4 mol / L.
3. The method according to claim 1, wherein: The thorium-232 decay chain material is a thorium salt or a thorium oxide.
4. The method according to claim 3, wherein: The thorium salt is hydrated thorium nitrate.
5. The method according to claim 1, wherein: Halogen ions exist in the form of Cl - Br - or I - acids or salts.
6. The method according to any one of claims 1 to 5, characterized in that: The anion exchange resin is a silica-based anion exchange resin.
7. The method according to claim 6, wherein: The preparation method of the silicon-based anion exchange resin comprises the following steps: 4-vinylpyridine and divinylbenzene undergo an in-situ solution copolymerization reaction in the presence of an initiator and a diluent in porous SiO2 channels to obtain silicon-based polyvinylpyridine; and the silicon-based polyvinylpyridine undergoes a methylation reaction with dimethyl sulfate to obtain the silicon-based anion exchange resin.
8. The method according to claim 6 or 7, wherein: The effective particle size of the silica-based anion exchange resin is 37-150 μm, and the BET specific surface area is 50-80 m 2 / g, and the average pore size is 10~50 nm.
9. The method according to any one of claims 1 to 5, characterized in that: When separating lead-212, the elution reagent is an aqueous solution with a salt concentration or acid concentration less than 0.5 mol / L; when separating bismuth-212, the elution reagent is a nitric acid solution with a concentration greater than 0.5 mol / L.
10. The method according to claim 9, wherein: When separating lead-212, the eluent is ultrapure water; when separating bismuth-212, the eluent is 1.0 M nitric acid.
Citation Information
Patent Citations
Alpha-particle emitter removal
CN102800378A
Separation and recovery method for thorium and uranium by using silicon-based anion exchange resin
CN103589866A
Silicon-based anion exchange resin and preparation method thereof
CN111269339A
Method for separating thorium from spallation elements
CN117051271A
Adsorption chromatography material for technetium in radioactive waste liquid and preparation method thereof
CN117463306A
Cited By
Radiation-resistant separation material for thorium-barium separation and preparation method thereof
CN121016701A
Radiation resistant separation material for thorium-barium separation and method of making the same
CN121016701B
Method for extracting high-purity lead-212 based on decay chain of thorium nitrate
CN121496191A
Automatic leaching control system for lead 212 radioactive isotope
CN121523172A
Method for separating and extracting lead-212 and bismuth-212 by anion exchange fibers
CN122252015A
